Calibration of Hunters' Impressions with Female Caribou Body Condition Indices to Predict Probability of Pregnancy - Lyver, P.O'B.; Gunn, A. (ARCTIC, 2004)
Aboriginal harvests of barren-ground caribou (Rangifer tarandus) potentially offer a large sample for assessing body condition. The purpose of this study was to determine the probability that a certain amount of fat would be at designated anatomical sites when Dënesóline hunters qualitatively report the condition of an animal. Hunters' impressions were used to evaluate the condition of adult female barren-ground caribou (R. t. groenlandicus) in late winter. A semi-objective body condition index (BCI) was developed using fat indices described by biologists as useful for measuring caribou body condition. Fat deposits from 217 adult female caribou harvested in late winter (41 in 2000 and 176 in 2001) were used to calibrate hunters' impressions with BCI estimates. Variation in hunters' impressions and BCI estimates indicated that adult female caribou were fatter in 2000 than in 2001. Multinomial log-linear models indicated that hunters' impressions were related to each of the variables that make up BCI. The probability of pregnancy was significantly related to both BCI and hunters' impressions in 2000 and in 2001. Both models indicated that fat adult female caribou had a greater probability of being pregnant than thin cows. Monitoring of barren-ground caribou body condition provides common ground for northern aboriginal communities and government biologists to collaboratively manage a wildlife resource. Les prélèvements du caribou des toundras (Rangifer tarandus) par les Autochtones pourraient offrir un vaste échantillon permettant d'évaluer l'état corporel. Cette étude avait pour but de déterminer la probabilité qu'une certaine quantité de gras soit présente dans des zones anatomiques désignées, au moment où les chasseurs Dënesóline font un rapport qualitatif sur la condition physique d'un animal. On a eu recours aux opinions des chasseurs pour évaluer l'état physique du caribou femelle des toundras à l'âge adulte (R. t. groenlandicus) à la fin de l'hiver. On a créé un index semi-objectif de l'état corporel (IEC) ...